Orbital hopping maneuvers with two Astrobee free-flyers: Ground and flight experiments - Kwok-Choon, Stephen; Hudson, Jennifer; Romano, Marcello (Frontiers in Robotics and AI, 2022)
Dynamic hopping maneuvers through mechanical actuation are proposed as a method of locomotion for free-flyer vehicles near or on large space structures. Such maneuvers are of interest for applications related to proximity maneuvers, observation, cargo carrying, fabrication, and sensor data collection. This paper describes a set of dynamic hopping maneuver experiments performed with two Astrobees. Both vehicles were made to initially grasp onto a common free-floating handrail. From this initial condition, the active Astrobee launched itself through mechanical actuation of its robotic arm manipulator. Presented are the results from ground and flight experimental sessions completed at the Spacecraft Robotics Laboratory of Naval Postgraduate School, the Intelligent Robotics Group facility at NASA Ames, and hopping maneuvers aboard the International Space Station. Overall, this paper demonstrates that locomotion through mechanical actuation was able to successfully launch a free-flyer vehicle in an initial desired trajectory from another object of similar size and mass.